2017
DOI: 10.3892/etm.2017.4884
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of controlled release of cytokine response modifier A from chitosan microspheres on rat chondrocytes from interleukin-1β induced inflammation and apoptosis

Abstract: Abstract. The aim of the present study was to investigate the protective effect of cytokine response modifier A (CrmA) released from chitosan (CS) microspheres in a controlled manner on interleukin (IL)-1β-induced inflammation and apoptosis in chondrocytes. The CrmA release kinetics were characterized by an initial burst release, which was reduced to a linear release over 8 days. Furthermore, chondrocytes were isolated from 1-week-old Sprague Dawley rats. The cell culture was established by stimulation with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Thus, CrmA might exert potential therapeutic effects on OA. Our previous study revealed that the controlled release of CrmA from chitosan (CS) microspheres could suppress chondrocyte inflammation and apoptosis induced by IL-1β in vitro [13]. However, the effects of CrmA on OA-related synovitis and cartilage damage in vivo remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CrmA might exert potential therapeutic effects on OA. Our previous study revealed that the controlled release of CrmA from chitosan (CS) microspheres could suppress chondrocyte inflammation and apoptosis induced by IL-1β in vitro [13]. However, the effects of CrmA on OA-related synovitis and cartilage damage in vivo remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of pDNA-CrmA release from the HA/CS-CrmA nanoparticles was measured by dissolving HA/CS-CrmA nanoparticles in phosphate-buffered saline (pH 7.4) at 37 °C in a shaker bath at 135 rpm. At appropriate time intervals (1,4,7,10,13,16,19, and 22 days), samples were centrifuged to collect the supernatants for analysis. The amount of pDNA-CrmA released into the supernatant was determined by spectrophotometer (DU640; Beckman, Fullerton, CA, USA) at 260 nm.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%